LONGITUDINAL ELLIPSOID ZONE DYNAMICS AFTER MACULAR HOLE REPAIR IN THE DISCOVER STUDY: Structure–Function Assessment. Issue 5 (May 2021) - Sevgi, Duriye Damla; Yee, Philina S.; Srivastava, Sunil K.; Le, Thuy K.; Abraham, Joseph R.; Reese, Jamie; Ehlers, Justis P.
Abstract : Purpose: To evaluate association of the baseline macular hole (MH) geometric features and longitudinal ellipsoid zone integrity with the visual acuity outcome after surgical repair. Methods: This was a post-hoc analysis of eyes in the DISCOVER study undergoing vitrectomy repair for MH. Anatomical and functional data were collected through one year postoperatively. An automated retinal layer segmentation platform was used for the assessment of outer retinal metrics and volumetric reconstruction of MH. Association of longitudinal ellipsoid zone features and baseline MH height, width, and volume with VA outcomes were investigated. Results: Eighty-four eyes with MH were included. The mean baseline VA was 20 of 114 and increased to 20 of 45 ( P < 0.001) at postoperative Month 12 (N = 45). Successful MH closure was achieved in 98.8% of cases. Ellipsoid zone integrity metrics significantly improved from baseline ( P = 0.002) and postoperative Month 1 ( P < 0.001) to post-operative Month 12. Ellipsoid zone metrics independently correlated with VA at all follow-up visits ( P < 0.05). Increased baseline MH width and volume negatively correlated with the VA at postoperative Month 12 ( P < 0.001). Preoperative VA and EZ integrity on optical coherence tomography were predictors for postoperative VA. Conclusion: Baseline MH volumetric parameters and EZ parameters were associated with VA outcomes after repair. Abstract : Baseline macular hole geometric features and longitudinal ellipsoid zone integrity are associated with visual acuity outcomes after intraoperative optical coherence tomography-assisted macular hole repair.